You have new items in your feed. Click to view.
Q: Applying PEMDAS, simplify this expression 6+4(3^2)-20
A: 6 + (4 * (3^2)) - 20 = 22
Question
Updated 6/26/2014 11:22:42 AM
Rating
3
6+4(3^2)-20
=(6+4×3^2)-20
=(6+4×9)-20
=(6+36)-20
=42-20
=22

Questions asked by the same visitor
Applying PEMDAS, simplify this expression 9+4(10/2)-6
Weegy: 9 + 4 (10 / 2 ) ? 6 =9 + 4 (6) - 6 =9 + 24 - 6 = 27 (More)
Question
Updated 6/16/2014 2:41:35 PM
9 + 4(10/2) - 6 = 9 + 4(5) - 6 = 9 + 20 - 6 = 29 - 6 = 23
Confirmed by andrewpallarca [6/16/2014 2:50:11 PM]
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 247 [Total 265] Ratings 0 Comments 177 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 125 [Total 276] Ratings 1 Comments 5 Invitations 11 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.